The Role of Social Media in Increasing Customer Interaction and Brand Loyalty - Nasaruddin Siregar; Sari Endah Nursyamsi; Filda Angellia; Maria Jashinta Elisabet Hamboer; Mayang Riyantie (Jurnal Minfo Polgan, 2023)
Social media has become a huge phenomenon in today's digital age. This phenomenon has changed the way customers interact with brands and products. In this context, this research aims to investigate the role played by social media in enhancing customer interaction and brand loyalty. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that in an increasingly competitive business world, the role of social media in increasing customer interaction and brand loyalty is very significant. Social media has opened up new opportunities for companies to communicate with customers, build emotional connections, provide better customer service, and measure the effectiveness of their strategies. All of these contribute to the creation of strong customer loyalty, which is a valuable asset in the long run for a brand.